Development of Higher-order Thinking Skills-Based Test Instruments on Internasional Trade Materials - Putri, Risma Ananda; Fitrayati, Dhiah (Journal Intellectual Sufism Research (JISR), 2021)
This research is research on developing a test instrument based on higher-order thinking skills on international trade material. The objectives of this development are 1) to develop a test instrument based on higher-order thinking skills; 2) measure the validity and reliability of the test instrument; 3) identify differentiating power and level of difficulty of the test instrument; and 4) measuring the effectiveness of the test instrument distractors. This development uses the Borg & Gall development model consisting of potentials and problems, data collection, product design, design validation, design revision, revision collection, product revision, use trial, and product revision. The results showed that the 10 questions were valid and reliable with the result that the validity value of each question was more than 0.338 and the reliability was 0.655. The results of the test quantity of questions consisting of differentiating power, level of difficulty, and effectiveness of distractors showed that the questions were by following per under the characteristics of higher-order thinking skills.